2011
DOI: 10.3324/haematol.2010.036715
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in elderly patients with acute myeloid leukemia: patients may be more accurate than physicians

Abstract: patients aged more than 60 years with de novo acute myeloid leukemia were enrolled in a prospective observational study. Two different quality of life instruments were employed: the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire -C30 (EORTC QLQ-C30) and a health-related quality of life questionnaire for patients with hematologic diseases (QOL-E). ResultsForty-eight patients (42.4%) received intensive chemotherapy and 65 (57.6%) were given palliative treatments. Age gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 26 publications
4
55
0
1
Order By: Relevance
“…45,47 In this context, Oliva et al reported a study on elderly AML patients in which QOL physical functioning was of prognostic relevance yet, somewhat surprisingly, did not correlate to the physician-assessed ECOG performance status. 48 While the item 'fatigue' has been shown to be prognostically relevant in several different malignant diseases, 47,[49][50][51] so far only hypotheses to explain the mechanisms underlying the association between reported data on patient health status and duration of survival have been proposed. 52 'Fatigue' is a patient-reported outcome and multi-faceted concept including both mental and physical components whose critical domains have not been sufficiently standardized and for which several scales have been developed.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…45,47 In this context, Oliva et al reported a study on elderly AML patients in which QOL physical functioning was of prognostic relevance yet, somewhat surprisingly, did not correlate to the physician-assessed ECOG performance status. 48 While the item 'fatigue' has been shown to be prognostically relevant in several different malignant diseases, 47,[49][50][51] so far only hypotheses to explain the mechanisms underlying the association between reported data on patient health status and duration of survival have been proposed. 52 'Fatigue' is a patient-reported outcome and multi-faceted concept including both mental and physical components whose critical domains have not been sufficiently standardized and for which several scales have been developed.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…However, while Deschler et al 2 found "fatigue" to be an independent predictor of survival, Oliva et al 5 found "physical functioning" to be so (both scales stemming from the EORTC QLQ-C30). In the study of Oliva et al, 5 however, the analysis did not control for a key previously known prognostic factor for AML patients (i.e. cytogenetics) thus significantly limiting the possibility of drawing conclusions about the actual independent prognostic value of PROs.…”
mentioning
confidence: 99%
“…Interestingly, two papers recently published in this Journal exemplify this complex scenario and show how challenging it is to draw conclusions from such studies. The Deschler et al study 2 included patients with AML, as did the other study by Oliva et al, 5 and both investigated the prognostic value of PROs at baseline in the same cancer population. Both studies included patients with AML over 60 years of age and used, among other instruments, the same PRO measure (i.e.…”
mentioning
confidence: 99%
“…It has been reported that patients with acute myeloid leukaemia on treatment have a median EORTC QLQ-C30 global health status/QoL score of 50 (Oliva et al, 2011), similar to that observed at baseline for both arms of COMFORT-II: the median baseline score for each arm was 50. In particular, fatigue is a major factor of the poor HRQoL of patients with MF (Mesa et al, 2007b), and the baseline data for COMFORT-II showed that it had the highest score (most severe) of the nine symptom scales for the EORTC QLQ-C30 {mean [standard deviation (SD)] of 44Á4 [27Á6] for ruxolitinib-treated patients and 51Á2 [28Á7] for BAT-treated patients}.…”
Section: Hrqol In Patients With Mf From Comfort-ii ª 2013 John Wiley mentioning
confidence: 84%